Detection of the early stage of spontaneous hemopneumothorax by CT attenuation values. Issue 7 (20th April 2020) - Koike, Yukiko; Namkoong, Ho; Otake, Sotaro; Asamura, Hisao
Abstract: Spontaneous hemopneumothorax is potentially fatal and can mimic spontaneous pneumothorax when changes in vital signs and bloody discharge from the chest tube are absent. Attenuation values at computed tomography may help detect this condition. Abstract : Spontaneous hemopneumothorax is potentially fatal and can mimic spontaneous pneumothorax when changes in vital signs and bloody discharge from the chest tube are absent. Attenuation values at computed tomography may help detect this condition.